3‐MCPD‐ and glycidyl esters can be mitigated in vegetable oils by use of short path distillation. Issue 3 (13th June 2015) - Pudel, Frank; Benecke, Patrick; Vosmann, Klaus; Matthäus, Bertrand
Abstract : Short path distillation was applied to produce edible oils low in 3‐MCPD‐FE and G‐FE, but with comparable quality to conventionally deodorized oils. By use of the Response Surface Methology the effect of different process parameters (condenser temperature (X1 ), evaporator temperature (X2 ), stirrer speed (X3 ) and pump frequency (X4 )) on quality parameters of the oil (content of 3‐MCPD‐FE/G‐FE (minimal), acid value (minimal), content of vitamin‐E‐active compounds (sum of tocopherols and tocotrienols, maximal) and oxidation stability (maximal)) was investigated. A model was calculated for the production of refined palm oil with lowest amounts of 3‐MCPD‐FE/G‐FE and a chemical and sensory quality comparable to oil produced by standard deodorization. For the different variables of short path distillation no 3‐MCPD‐FE was detected in any of the samples, while the level for G‐FE ranged between the limit of detection and 0.7 mg/kg. A target conflict between the content of vitamin‐E‐active compounds (maximal) and acid value (minimal) was found, but in a (global) optimum of all target quality parameters (condenser temperature = 60°C, evaporator temperature = 170°C, stirrer speed = 100 rpm and pump frequency = 20 Hz) the quality of the short path distilled palm oil was comparable to conventionally refined palm oil. Slightly poorer sensory quality regarding taste and smell can be improved by a mild deodorization after short path distillation. Only the colour of the resulting oil differs from that of a conventionally refined oil, one being orange red due to the carotinoids which were not thermally decomposed. Practical Application: Mitigation of 3‐MCPD‐FE and G‐FE is a big issue in oil processing. Especially for sensible products such as baby food the content of the esters should be as low as possible without changing the quality of the edible oil. Short path distillation is known as a gentle method used for the enrichment and purification of heat‐sensitive compounds. Thus the application of short path distillation on the purification of edible oils within the refining process could be an interesting option for the production of oils low in 3‐MCPD and glycidyl esters while maintaining high oil quality. Use of Response Surface Methology short path distillation followed by mild deodorization (180°C, 120 min) has been optimized to obtain edible oils low in 3‐MCPD‐FE and G‐FE but with comparable oil quality to conventionally deodorization. Only the red colour of palm oil was not reduced by this procedure. Abstract : Use of Response Surface Methology short path distillation followed by mild deodorization (180°C, 120 min) has been optimized to obtain edible oils low in 3‐MCPD‐FE and G‐FE but with comparable oil quality to conventionally deodorization. Only the red colour of palm oil was not reduced by this procedure.